PLATFORMIZATION OF DOMESTIC WORK: A STUDY ON WORKING CONDITIONS AND SUBJECTIVITY OF DOMESTIC WORKERS IN PLATFORM COMPANIES - Pavan, Carolina (2024)
The purpose of this study is to analyze the new forms of labor subordination experienced by domestic Workers operating through apps and digital platform companies. Given the contexto of intensified datafication and financialization of everyday life and neoliberal hegemony, there is a need to undertand how the socio-sexual Division of labor functions in this scenario. With the rise of the platformization of labor and the intensification of uberization, new forms of control, management, and subordination of labor are being employed, exacerbating the precariousness and informalization of workers. In the contexto of platformization of domestic work, domestic Workers, who already faced a precarious and undervalued work reality, are now doubly subordinated: by the client and by the platform company. The research began with a bibliographic and documentar review of the Terms of Use of platform companies and is currently using na active online questionnaire to profile the women working through these platforms. Initial data frm the questionnaire may suggest some hypotheses, such as changes in the profile of workers who are domestic workers through apps in terms of age and race, and that the characteristics of informalization and precariousness of domestic work are manifesting in the contexto of labor platformization.